Reflection of Myth: A Comparative Study of Mehdi Akhavan-Sales and Adoni - Sadoughi, Shirin (2021)
The objective of this article was a comparative study of the representations of myth in the poems of Mehdi Akhavan Sales and Adonis (Syrian poet). The research method is a bibliographic one and also analytical-descriptive. Relying on the techniques of myth-making and symbolism and their artistic and literary aesthetics, Adonis seeks to include his personality in mythical symbols, albeit briefly and concisely, and turns myth into a kind of contemporary or historical reality. The bond of Akhavan poetry with the myths, archetypes and symbols of Iran and the use of Persian words, compounds and expressions, in most of his poems, is one of his poetic arrangements which has given an epic status to his poetic language which express a critical note with virtuosity and power of epic language. Results show that Akhavan employs historical myths of ancient Iran. Adonis also took advantage of Arab mythology and was deeply influenced by the society in which he grew up, combining it with national and patriotic issues and creating successful mythological and epic archetypes. According to results, Adonis has referred to different cultures such as Greece, ancient Egypt, biblical myths and pre-Islamic myths, while Akhavan speaks only of the myths of ancient Iran.